Associations between cerebrovascular risk factors and parkinson disease. Issue 4 (29th August 2019) - Kummer, Benjamin R.; Diaz, Iván; Wu, Xian; Aaroe, Ashley E.; Chen, Monica L.; Iadecola, Costantino; Kamel, Hooman; Navi, Babak B.
Abstract : Objective: To determine whether cerebrovascular risk factors are associated with subsequent diagnoses of Parkinson disease, and whether these associations are similar in magnitude to those with subsequent diagnoses of Alzheimer disease. Methods: This was a retrospective cohort study using claims data from a 5% random sample of Medicare beneficiaries from 2008 to 2015. The exposures were stroke, atrial fibrillation, coronary disease, hyperlipidemia, hypertension, sleep apnea, diabetes mellitus, heart failure, peripheral vascular disease, chronic kidney disease, chronic obstructive pulmonary disease, valvular heart disease, tobacco use, and alcohol abuse. The primary outcome was a new diagnosis of idiopathic Parkinson disease. The secondary outcome was a new diagnosis of Alzheimer disease. Marginal structural Cox models adjusting for time‐dependent confounding were used to characterize the association between exposures and outcomes. We also evaluated the association between cerebrovascular risk factors and subsequent renal colic (negative control). Results: Among 1, 035, 536 Medicare beneficiaries followed for a mean of 5.2 years, 15, 531 (1.5%) participants were diagnosed with Parkinson disease and 81, 974 (7.9%) were diagnosed with Alzheimer disease. Most evaluated cerebrovascular risk factors, including prior stroke (hazard ratio = 1.55; 95% confidence interval = 1.39–1.72), were associated with the subsequent diagnosis of Parkinson disease. The magnitudes of these associations were similar, but attenuated, to the associations between cerebrovascular risk factors and Alzheimer disease. Confirming the validity of our analytical model, most cerebrovascular risk factors were not associated with the subsequent diagnosis of renal colic. Interpretation: Cerebrovascular risk factors are associated with Parkinson disease, an effect comparable to their association with Alzheimer disease. ANN NEUROL 2019;86:572–581